Clinical characteristics and treatment outcomes of benign laryngeal lesions: a retrospective observational study from a tertiary care centre - Hiranya Prova Saikia; Nilmoni Nath; Maitrayee Deb; Debajyoti Das (International Journal of Research in Medical Sciences, 2026)
Background: The larynx is a complex organ of the upper aerodigestive tract responsible for phonation, respiration, and airway protection. Benign laryngeal lesions commonly present with hoarseness of voice and significantly affect quality of life. Early diagnosis and appropriate management are essential to restore normal vocal function and prevent chronic morbidity. Methods: A retrospective observational study was conducted in the department of otorhinolaryngology, Assam Medical College and Hospital, Dibrugarh, from January 2024 to June 2025. Thirty patients with benign laryngeal lesions were evaluated based on clinical presentation, etiological factors, type of lesion, management, and treatment outcomes. Diagnosis was confirmed by laryngoscopic examination and histopathological analysis where indicated. Results: The majority of patients belonged to the 25-48 years age group, with slight male predominance. Teachers constituted the largest occupational group (33.33%). Vocal abuse was the most common etiological factor (40%). Hoarseness of voice was the predominant presenting symptom. Vocal cord polyp was the most common lesion (36.7%), followed by vocal cord nodules (30%). Microlaryngeal surgery was performed in 46.7% of patients, while the remainder improved with conservative treatment including voice rest and speech therapy. Conclusions: Benign laryngeal lesions are commonly associated with vocal abuse and predominantly affect individuals in the productive age group. Early diagnosis, vocal hygiene, and timely intervention provide favorable outcomes and help prevent chronic voice disorders.